2010
DOI: 10.17660/actahortic.2010.849.24
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Psidium Guajava L. Using Micropropagation

Abstract: Here we describe an innovative, reproducible, and inexpensive method for in vitro cloning of guava using nodal stems segments. A novel process was established for completely inhibiting phenol-based browning by coating the explants at their cut ends with commercial silicon. A high regeneration frequency (98.33%) was achieved on MS medium supplemented with 4 mg/L BA and 0.4 mg/L IAA, with a maximum average number of 76.17 shoots per explant produced on the third subculture. The highest rooting percentage (95.83%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Phenolic oxidative tissue browning is one of the bottlenecks in woody plant tissue culture. In guava, tissue browning was completely prevented by sealing the nodal explants cutting ends with Si (Youssef et al, 2010). Addition of Si as K 2 SiO 3 to MS medium reduced the hyperhydricity in Cotoneaster wilsonii plant by decreasing the content of MDA in the regenerated shoots when compared with the control (Sivanesan et al, 2011).…”
Section: Results and Discussiunmentioning
confidence: 99%
“…Phenolic oxidative tissue browning is one of the bottlenecks in woody plant tissue culture. In guava, tissue browning was completely prevented by sealing the nodal explants cutting ends with Si (Youssef et al, 2010). Addition of Si as K 2 SiO 3 to MS medium reduced the hyperhydricity in Cotoneaster wilsonii plant by decreasing the content of MDA in the regenerated shoots when compared with the control (Sivanesan et al, 2011).…”
Section: Results and Discussiunmentioning
confidence: 99%
“…Phenolic oxidative tissue browning is one of the bottlenecks in woody plant tissue culture. In guava, tissue browning was completely prevented by sealing the nodal explants cut ends with Si (Youssef et al, 2010) and there was no detrimental effect of Si on the subsequent steps of in vitro propagation. The authors suggested that Si could be used during explants preparation to control phenolic tissue browning in other plants.…”
Section: Growth and Developmentmentioning
confidence: 99%
“…Cluster analysis was carried out on similarity estimates using the unweighted pair-group method with arithmetic average (UPGMA) software. These methods were carried out using MVSP software programs as in Youssef (2004). The results were then represented as a dendrogram for allover primers.…”
Section: Discussionmentioning
confidence: 99%